Family in The Shining - Bureš, Michal (Univerzita Pardubice, 2023)
The thesis attempts to examine the motifs of family in the novel The Shining (1977) by Stephen King. The theoretical part focuses on the categorization of horror novels in terms of literary theory and the occurrence of motifs of dysfunctional families and domestic violence in horror literature universally. Furthermore, it includes a general introduction to the concept of family as well as to its role in 20th-century America with a strong emphasis on the contemporary consensus regarding dysfunctional families and domestic violence. The analytical part then explores such motifs in The Shining and interprets the possible criticism of contemporary American society.
Rodina v románu Osvícení
Keywords: hororová literatura; rodina; domácí násilí; King, Stephen; Osvícení; horror literature; family; domestic violence; King, Stephen; The Shining